-86 = -6(-3p - 3) - 5p
Distribute the -6 into the parentheses:
-86 = (-6 * -3p) + (-6 * -3) - 5p
-86 = 18p + 18 - 5p
Simplify:
-86 = 13p + 18
Subtract both sides by 18:
-86 - 18 = 13p + 18 - 18
-104 = 13p
Divide both sides by 13:
=
![(-104)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v8gssuxnc6ojp0nak2yu7nsgcnrt93shcc.png)
=
![(-8)/(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4o5pqllkrh1urvbccxo1g5v665nk731mlx.png)
p = -8
Good luck! If you have any questions, don't be afraid to ask :))
-T.B.